PENERAPAN MIND MAP UNTUK PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA JERMAN SISWA KELAS XI-BAHASA SMAN 1 GEDANGAN SIDOARJO - Novasari, Avika (LATERNE, 2018)
Speaking is a form of oral communication. Speech skills are conducted in language learning, especially in German. One of the Basic Competencies in the Curriculum 2013, students are required to produce interaction textual oral transactions and write according to the theme specified in Curriculum 2013. Learning to speak German requires an effort to create learning effectively. Learning to speak can be through a learning technique. Learning technique in question is Mind Map. This is because Mind Map is useful for developing ideas through concept maps. Mind map technique was chosen in this study to encourage students to express their ideas that will be presented orally. A problem formulation in this research is how the learning process of German speaking skills of students of grade XI-Language SMAN 1 Gedangan sidoarjo using mind map. The purpose of this study describes the learning process of German speaking skills of students of grade XI-Language SMAN 1 Gedangan Sidoarjo using mind map. This type of research uses qualitative research methods described descriptively. This research data is data of observation result and questionnaire of student response. The results of this study indicate that the effective mind map used in learning German language skills in students of grade XI-Language SMAN 1 Gedangan Sidoarjo. This is evidenced by the application of mind map on learning German speaking skills second meeting is better than the application of mind map on learning German speaking skills first meeting.  The result of questionnaire of student response after application of mind map on learning German speaking skill is mind map gives many benefits to help learners express their ideas presented orally. Mind map technique is expected to add variations of teacher teaching technique to be more creative and innovative, so the motivation to learn German students increased and positive impact on student learning outcomes. Keywords: speaking skills, learning technique, mind map.